PELAKSANAAN POS UPAYA KESEHATAN KERJA DI WILAYAH KERJA PUSKESMAS PAAL MERAH I KOTA JAMBI - Aslamiyah, Dita; Witri, Repelita (LPPM Universitas Jambi, 2023)
ABSTRACTBackground: The world organization, the International Labor Organization (ILO), says that 2.78 million workersdie every year due to work accidents and work-related diseases. In Indonesia, the number of cases of work-relateddiseases has increased. Given the high risk of occupational health and safety for workers and the mandate in thelaw to implement occupational health in the workplace, it is necessary to implement occupational health efforts inthe work area of the Puskesmas. One of the forms of work health efforts at the puskesmas is the establishment ofthe Occupational Health Efforts Post (UKK Post). In practice, the roles of cadres and program holders from thePuskesmas have not run properly. Based on data on the Performance Achievement of the 1st Quarter of the PaalMerah 1 Health Center in 2023 related to the low number of sick workers served by 18.26%.Method: The data collected by the author is to provide information regarding the description of the implementationof the UKK Post, which consists of two types, namely Primary Data and Secondary Data.Result and Conclusion The benefit of implementing the UKK Post for Respondents is that workers in theineffective category have the greatest frequency of 32 people with a percentage of 77.5%.Keywords: worker, occupational health post, Health Center, JambiABSTRAKLatar Belakang: Organisasi dunia International Labour Organization (ILO) manyampaikan bahwa 2,78 juta pekerjameninggal setiap tahun karena kecelakaan kerja dan penyakit akibat kerja.Di Indonesia jumlah kasus penyakitakibat kerja mengalami peningkatan. Mengingat tingginya risiko kesehatan dan keselamatan kerja bagi pekerjadan adanya amanat dalam Undang-Undang undang untuk menerapkan kesehatan kerja di tempat kerja, makaperlu dilaksanakannya upaya Kesehatan kerja di wilayah kerja Puskesmas. Bentuk upaya kesehatan kerjapuskesmas salah satunya dibentuknya Pos Upaya Kesehatan Kerja (Pos UKK). Pada pelaksanaannya, perankader maupun pemegang program dari Puskesmas belum berjalan semestinya. Berdasarkan data PencapaianKinerja Puskesmas Triwulan 1 Puskesmas Paal Merah 1 Tahun 2023 terkait rendahnya angka pekerja sakit yangdilayani sebesar 18,26%.Metode: Data yang dikumpulkan penulis untuk memberikan informasi mengenai gambaran pelaksanaan Pos UKK,yang terdiri dari dua jenis, yaitu Data Primer dan Data Sekunder. Hasil dan Kesimpulan: Manfaat pelaksanaanPos UKK Bagi Responden yaitu pekerja dengan kategori belum efektif memiliki frekuensi paling besar yaitusebanyak 32 orang dengan presentase sebesar 77,5 %.Kata Kunci: Pekerja, Pos Upaya Kesehatan Kerja, puskesmas, jambi